Prolonging lifetime of wireless sensor networks with mobile base station using particle swarm optimization - Nurul Adilah, Abdul Latiff; Nurul Mu’azzah, Abdul Latiff, Dr.; R. Badlishah, Ahmad, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/